Target Capture and Massive Sequencing of Genes Transcribed in Mytilus galloprovincialis - Rosani, Umberto (Hindawi Publishing Corporation, 2014)

(untitled)
Next generation sequencing (NGS) allows fast and massive production of both genome and transcriptome sequence datasets. As the genome of the Mediterranean mussel Mytilus galloprovincialis is not available at present, we have explored the possibility of reducing the whole genome sequencing efforts by using capture probes coupled with PCR amplification and high-throughput 454-sequencing to enrich selected genomic regions. The enrichment of DNA target sequences was validated by real-time PCR, whereas the efficacy of the applied strategy was evaluated by mapping the 454-output reads against reference transcript data already available for M. galloprovincialis and by measuring coverage, SNPs, number of de novo sequenced introns, and complete gene sequences. Focusing on a target size of nearly 1.5 Mbp, we obtained a target coverage which allowed the identification of more than 250 complete introns, 10,741 SNPs, and also complete gene sequences. This study confirms the transcriptome-based enrichment of gDNA regions as a good strategy to expand knowledge on specific subsets of genes also in nonmodel organisms.